2023
DOI: 10.1177/24741264231157231
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Arterial Macroaneurysm in a Patient With Lynch Syndrome

Abstract: Purpose: To describe a case of retinal arterial macroaneurysm (RAM) in a patient with hereditary nonpolyposis colon cancer (HNPCC)/Lynch syndrome. Methods: A case and its findings were analyzed. Results: A 68-year-old woman presented with a recent history of decreased near vision in the left eye. Both eyes had a visual acuity of 20/20 with normal intraocular pressure. The right retina was normal. The left retina had a focal dilation of the retinal arteriole with a surrounding hemorrhage and lipid in the infero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
1
Order By: Relevance
“…In our study, we observed 6 newborns with this condition (out of 3,500 newborn girls), which is higher than expected according to the literature. The incidence of 47,XYY syndrome in our study (7/3,500 newborn boys) was also higher than that reported in literature (1 in 1,000 males) 43 . The discrepancy could be partially explained by the advanced parental age being previously reported in multiple studies as a risk factor for sex chromosomal abnormalities [44][45][46] .…”
Section: Clinical Management Of Patients With Positive Genetic Screen...contrasting
confidence: 61%
“…In our study, we observed 6 newborns with this condition (out of 3,500 newborn girls), which is higher than expected according to the literature. The incidence of 47,XYY syndrome in our study (7/3,500 newborn boys) was also higher than that reported in literature (1 in 1,000 males) 43 . The discrepancy could be partially explained by the advanced parental age being previously reported in multiple studies as a risk factor for sex chromosomal abnormalities [44][45][46] .…”
Section: Clinical Management Of Patients With Positive Genetic Screen...contrasting
confidence: 61%